Evaluation of yeast culture and direct-fed microbial on gut histology and serum components of broilers challenged with suboptimal diets under heat stress (Acta Scientiarum. Animal Sciences, 2019)
The use of antibiotics in feed for growth promotion has been restricted in many countries, thus it is of interest to investigate potential alternatives for enhancing growth performance in birds. An experiment was carried out to evaluate the concurrent use of prebiotic and probiotic on gut histology and some blood chemicals of broiler chickens during heat stress. A total of 144 day-old male Ross 308 broiler chicks were randomly divided into 3 treatments. The first treatment was a diluted diet including rice bran without probiotic or prebiotic. The other treatments were fed the diluted diets with a prebiotic (treatment 2) and concurrent use of that prebiotic along with a probiotic (treatment 3). Results showed that villus height was not influenced by feed additives. However, crypt depth significantly increased by feed additives in particular with combination of prebiotic and probiotic. The ratio of villus height to crypt depth significantly decreased in treatments fed prebiotic alone or prebiotic and probiotic together. This finding is indicating the fact that non-starch polysaccharides (NSPs) in high inclusion rate of rice bran caused to villus height erosion. It could be concluded that prebiotic and probiotic caused an increasing of enterocyte proliferation in the crypt of Liberkhun.